Sustainable finance and the global health crisis - Falcone, Pasquale Marcello; Sica, Edgardo (Abingdon, Oxon Routledge, 2024)
The speed with which the various economies recover from the Covid-19 pandemic will significantly determine the economic pressure placed on the environment in the medium to long-term. Furthermore, the pandemic has highlighted the strong interrelations between natural and societal systems, with societal resilience depending on a resilient environmental support system. In this context, this book argues that the pandemic represents a wake-up call for financial systems to be better prepared for the climate crisis and social risk and has provided a stimulus to scale down the reliance of the global economy on fossil fuels. The first part of the book provides a deep and creative discussion between leading international researchers and experts on the policy options and financial instruments which can help to catalyze the green finance transition in the post Covid-19 era. The contributions here show that sustainable finance is emerging as a powerful tool to catalyze the transition towards a more environmentally and socially sustainable economic model. Instruments such as sovereign green bonds, green securities, and other sustainability-related securities can play a significant role in the post Covid-19 world to fund economic stimulus and to lead the way to new and more sustainable future. The second part of the book supports the debate by highlighting a number of selected case studies on financing transitions in different regional contexts including Africa, Asia, Europe , and Latin America. This book marks a significant contribution to the literature on environmental economics and finance, climate change and sustainability transitions"--
Contents: PART I: Perspectives and Policy Instruments - Policy Perspectives in Promoting Green Finance / Peterson K. Ozili - - Green Bonds for Innovation: The Entrepreneurial State and Sustainable Transition / Fabio Giudice and Piergiuseppe Morone - - The Role of Sustainable Finance During the Global Health Crisis: Transformative Innovation Policies for Environmental and Social Sustainability / Pasquale Marcello Falcone and Edgardo Sica - - How is the EU Financial System Getting Ready to take up the Climate Challenge? Some Answers from Science / Lucia Alessi and Serena Fatica - - No time to lie: Sustainable Finance Needs Nextgen Assurance / Simone Quatrain and Robert Costanza - - The EU Regulatory landscape on Sustainable Finance / Lucia Alessi and Georgios Papadopoulos - - PART II: Case Studies - ESG Investing During the Covid-19 Crisis: Evidence from Central European Stock Exchanges / Agnieszka Walachowska - - The Impact of Green Finance on Renewable Energy Consumption in the Covid-19 Pandemic / Henefa Shvydanenko, Oleg Shvydanenko, Ganna Duginets, Kateryna Boichenko, and Tatiana Busarieva - - Policy Perspectives on Greening of the Financial System: Implications for Ukraine / Oksana Makarchuk - - Sustainability and the Circular Economy: The Role of the Financial Sector and the Response of Inters Sanpaolo / Antonia Patrizia Iannuzzi, Stefania Sylos Labini, and Elisabetta D'Apolito - - Expanding Pathways for Green Finance to Support Regenerative Agriculture in Latin America / Sarah Gammage, Julian Rode, and Felipe Lesmes Palacio - - Social Dimension of Green Finance: Covid-19 Shines Spotlight on Companies' Vulnerable Employment in Supply Chains / Claudia Hitaj, Ioana-Stefania Popescu, Thomas Schaubroeck, and Thomas Gibon.
Includes bibliographical references and index.
Keywords: COVID-19 (Disease) -- Economic aspects; Finance -- Environmental aspects; Finance -- Social aspects